Understanding Sports Injuries Among Running Athletes In Gorontalo; Treatment Strategies And Prevention Efforts - Haryanto, Arief Ibnu; Duhe, Edy Dharma Putra; Hunta, Mohamad Akil; Umadji, Wahyu Ramadhan Putra; Abdelnaser, Moamen Mohamed Abdelgawad; Garcia-Carrillo, Exal (STAMINA, 2024)
This research aims to explore the understanding of running athletes in Gorontalo regarding sports injuries, including how they treat and prevent these injuries. By understanding the treatment strategies and prevention efforts used by athletes, this research hopes to provide useful insights to improve the well-being and performance of running athletes. This research use descriptive statistics with survey methods. This research was conducted at the Gorontalo City sports stadium (Merdeka Stadium). The population in this study were all running athletes who took shelter in that place. The total population was 20 athletes. The sample in this research was the entire athlete population. The instrument used in this research was a questionnaire whose validity and reliability have been tested by previous research. The data analysis technique uses descriptive statistics using SPSS version 25. After the descriptive data is obtained, it was categorized using the Norm Assessment Reference. The overall result is the largest percentage in the medium category. Based on these results, it suggests the need to increase education and training for athletes regarding sports injuries